MAKNA ORNAMEN KUMUDAWATI PENDHAPA AGENG MANGKUNEGARAN - Adisukma, Wisnu (Institut Seni Indoensia Surakarta, 2014)
This article aims to identify, comprehend, and explain the influence of Mangkunegaran fortress previouslythrough mind concept of Mangkunegara VII in initiative making of ornament kumudawati atPendhapa Ageng Mangkungaran; and symbolic meaning consisting of barbed in ornament kumudawatiwith Java culture order. Bearing in mind that culture is an element which influences the existence ofornament kumudawati, an overall understanding of the form, role, and meaning of ornament kumudawatiis based on the cultural approach that is a way of looking at culture as a system. According to thisresearch, Kumudawati ornament presented by Mangkunegara VII is the effort to dynamics Javaneseculture lofty values that is adiluhung and combined with western hesitant. Kumudawati ornament isassociated with the mind concept of Mangkunegara VII that the concept of counter culture and toacquire Javanese culture legality as adiluhung and dynamic although western culture as modernculture stays inside Javanese people.Keywords: Kumudawati Ornament, Meaning, Mangkunegara VII